Natural Existence of Endorhizospheric Bacteria Free from Atmospheric Nitrogen in the Endorhizosphere of Helianthus tuberosus and Smallanthus sonchifolius - Di Barbaro, María Gabriela; Del Valle, Eleodoro; Brandán de Weht, Celia (Current Topics in Agricultural Sciences Vol. 2, 2021)
The genus Azospirillum comprises free-living bacteria that inhabit soils of various ecological conditions, where they are often associated with the rhizosphere and endorhizosphere of plants. These bacteria have multiple attributes that can benefit host plants, due to their ability to fix atmospheric nitrogen (N2), secrete phytohormones such as auxins, cytokinins, and gibberellins. In addition, they can suppress populations of phytopathogenic microorganisms from the soil and decompose soil pollutants. Therefore, the objective of the work was to determine if topinambur (Helianthus tuberosus) and yacón (Smallanthus sonchifolius) plants grown in the Central Valley of the Province of Catamarca naturally have mutualistic symbiosis with endorhizospheric bacteria of the genus Azospirillum and / or with other genera of native atmospheric nitrogen-free fixing bacteria. Roots of each species were collected and the technique proposed by Döbereiner et al. [47] for the isolation of the N2-free binding endorhizospheric bacteria, Azospirillum sp. Native rhizobacteria of the genus Azospirillum were not isolated from the endorhizosphere of topinambur and yacón. The isolates obtained were characterized morphologically and physiologically, and three different morphotypes of each plant species were selected for their molecular identification. Eleven free fixing autochthonous microorganisms of atmospheric nitrogen present in the endorhizosphere of the study cultures were described, 6 in topinambur and 5 in yacón. All isolates belonging to the genus Pseudomonas. In topinambur, Pseudomonas sihuiensis and in yacón of Pseudomonas alcaligenes, P. resinovorans and P. sihuiensis. The natural colonization of the endorhizosphere of the cultures of topinambur (H. tuberosus) and yacón (S. sonchifolius) by autochthonous rhizobacteria of the genus Azospirillum could not be verified. The isolation of autochthonous atmospheric nitrogen-free fixing bacteria of P. sihuiensis, P. alcaligenes and P. resinovorans in the endorhizosphere of topinambur and yacón, cultivated in soils of the Central Valley of the Province of Catamarca, is reported for the first time.